Literacy Instruction Using Technology With Primary-Age Culturally and Linguistically Diverse Learners. (March 2015) - Musti-Rao, Shobana; Cartledge, Gwendolyn; Bennett, Jessica G.; Council, Morris
With continuing advances in the digital world, a variety of technologies are becoming easily accessible in the classroom. Although teachers may be using some of these technologies in their daily lives, they may not know how to incorporate these devices to support classroom learning. This article provides a guide for teachers interested in using technology to deliver supplemental literacy instruction in their classroom, particularly for primary-age students from culturally and linguistically diverse backgrounds. Benefits of using technology along with classroom applications are discussed.